Association of CSF Aβ38 Levels With Risk of Alzheimer Disease–Related Decline. (1st March 2022) - Cullen, Nicholas; Janelidze, Shorena; Palmqvist, Sebastian; Stomrud, Erik; Mattsson-Carlgren, Niklas; Hansson, Oskar; ,
Abstract : Background and Objective: Experimental studies suggest that the balance between short and long β-amyloid (Aβ) species might modulate the toxic effects of Aβ in Alzheimer disease (AD), but clinical evidence is lacking. We studied whether Aβ38 levels in CSF relate to risk of AD dementia and cognitive decline. Methods: CSF Aβ38 levels were measured in 656 individuals across 2 clinical cohorts: the Swedish BioFINDER study and the Alzheimer's Disease Neuroimaging Initiative (ADNI). Cox regression models were used to evaluate the association between baseline Aβ38 levels and risk of AD dementia in AD biomarker–positive individuals (AD+; determined by CSF phosphorylated tau [P-tau]/Aβ42 ratio) with subjective cognitive decline (SCD) or mild cognitive impairment (MCI). Linear mixed-effects models were used to evaluate the association between baseline Aβ38 levels and cognitive decline as measured by the Mini-Mental State Examination (MMSE) in AD+ participants with SCD, MCI, or AD dementia. Results: In the BioFINDER cohort, high Aβ38 levels were associated with slower decline in MMSE score (β = 0.30 points per SD, p = 0.001) and with lower risk of conversion to AD dementia (hazard ratio 0.83 per SD, p = 0.03). In the ADNI cohort, higher Aβ38 levels were associated with less decline in MMSE score (β = 0.27, p = 0.01) but not risk of conversion to AD dementia ( p = 0.66). Aβ38 levels in both cohorts were significantly associated with both cognitive and clinical outcomes when further adjusted for CSF P-tau or CSF Aβ42 levels. Discussion: Higher CSF Aβ38 levels are associated with lower risk of AD-related changes in 2 independent clinical cohorts. These findings suggest that γ-secretase modulators could be effective as disease-altering therapy. Trial Registration Information: ClinicalTrials.gov Identifier: NCT03174938.